Aktywność gospodarcza kobiet w Galicji w świetle „Skorowidza przemysłowo-handlowego” z 1912 roku. Zarys problematyki - Kozak, Szczepan (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2014)
Interest in the issues concerning women’s economic activity in Galicia has been rather limited so far. Historians’ attention has usually been drawn to the problem of employing them as factory workers. „Trade-industry index” developed at the beginning of the 20th century contains data on 2300 economic subjects operating in Galicia and run by women. Its analysis shows disproportions between province and the largest cities, It also draws attention to branches especially preferred by women as their domain like the clothing and food industries, clothes and food trade as well as restaurant-hotel services. However, as a historical source „Index” is significantly limited, that is why these results should be treated merely as a starting point for further research.